(untitled) (Philosophy and Progress, 2017)
This paper evaluates an ancient system of cosmology as a part of phenomenology of religion that is intrinsic to ancient Chinese philosophic attitude toward life. The ideas of the dynamic balance of opposites i.e. yin and yang duality, the supernatural force (the Tao) relating to the gradual development of events through a process of formulation, and thereby, acceptance of the inevitability of change are taken under consideration. In Chinese tradition, all forms of change are regarded as expressions of the interaction of two auxiliary forces (controlled by the Tao), the yin and the yang, between which equilibrium and harmony are assumed, as well as conflict and opposition. The yin-yang principles are regarded as the two major elements of Chinese cosmology: yin, being the femaleprinciple, and yang the male principle. The combination and interplay of these two opposites is believed by the Chinese to cause all universal phenomena i.e. the principal cause of creation. It is also demonstrated how this ancient Chinese supposition of yin and yang is used in different ways to serve different purposes. It is sometimes regarded as a system of divination that combines interacting forces designed to work as fortune telling devices. However, it is clarified how these facts the supreme reality (Shang-ti), supreme force (the Tao) and the auxiliary forces (yin-yang) work together in order to maintain the apparent harmony and order in nature as a whole. It is also generalized how these facts happened to be of great interest for the ancient Chinese thinkers. Philosophy and Progress, Vol#57-58; No#1-2; Jan-Dec 2015